(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: Several epidemiological studies have identified the association of abnormal ABPI with ischemic stroke. So the goal of this study was to determine the actual relationship of ABPI with ischemic stroke in the context of our country. Materials and Methods: This case control study was carried out in the Department of Neurology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh. ABPI was measured by Doppler ultrasound machine of 100 patients who were admitted to the Mitford Hospital during the study period. Among them 50 patients with Ischemic stroke, confirmed by CT/MRI scan of brain were considered as ‘case’ and 50 age- sex matched individuals with one or more vascular risk factors (VRF) but without stroke were considered as ‘control’. Then the results of ABPI were compared between the two groups. Results: Among the 50 patients with ischemic stroke (case group) , 74% had normal ABPI and 26% had ABPI< 0.9; on the other hand among 50 age and sex matched individuals (control group) 90% had normal ABPI and 10% had ABPI <0.9. The difference was statistically significant between two groups (p=<0.05).This association remained significant even after adjustment for potential confounders (age, gender, high BMI, hypertension, diabetes mellitus, hyperlipidemia, smoking, ischemic heart disease and family history) in a multiple logistic regression model. Conclusion: The incidence of low ABPI is significantly higher in ischemic stroke patients than the age- sex matched control. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 31-42